Primary brachial vein transposition for hemodialysis access: Report of a case and review of the literature. Issue 3 (8th November 2012) - Lambidis, Constantinos; Galanopoulos, Georgios
Abstract: The superiority of autogenous fistulae in patients with end‐stage renal disease, performing hemodialysis, is well established and largely accepted. However, in case that superficial veins in the upper arm are not available for fistula construction, brachial vein transposition may be a viable alternative prior to graft placement. This transposition could be done as a primary or staged procedure, depending on the vein size. We present the case of a 63‐year‐old male patient with a thrombosed arteriovenous graft in the forearm and a large brachial vein in the ipsilateral upper arm. A one‐stage (primary) brachial vein transposition was performed. The fistula, 10 months after its construction, is still patent. No complications have occurred.